Interdecadal summer warming of the Tibetan Plateau potentially regulated by a sea surface temperature anomaly in the Labrador Sea. (16th October 2020) - Gao, Kailun; Duan, Anmin; Chen, Deliang
Abstract: Downward clear‐sky longwave radiation, which is related to atmospheric water vapour content, has been suggested as an important factor causing an interdecadal increase in boreal summer surface temperature over the Tibetan Plateau (TP). We reveal the relationship between the 2 m air temperature (t2m) and water vapour over the TP in boreal summer, as well as the mechanism modulating the change in atmospheric water vapour. In recent decades, spatiotemporal variations between water vapour and t2m in boreal summer over the TP have shown synchronicity at the decadal scale. Moreover, Rossby wave trains which originate over the Northwest Atlantic and trigger an anomalous anticyclone between the northeastern TP and Baikal Lake are suggested to play a crucial role in decadal warming over the TP. First, the anomalous anticyclone, with an equivalent barotropic structure, can directly heat near‐surface air across the northeastern TP. Second, it promotes net water vapour input into the northeastern TP, leading to an increase of the total water vapour content over the entire TP, ultimately contributing to warming. Finally, a linear baroclinic model experiment further indicates that the Rossby wave trains are mainly associated with interdecadal increases in sea surface temperature (SST) in the Labrador Sea, with the SST in Baffin Bay playing a secondary role. Abstract : In recent decades, decadal spatiotemporal variations between water vapour and 2‐m air temperature in summer show synchronicity over the Tibetan Plateau (TP). The study reveals that Rossby wave trains which trigger an anomalous anticyclone over the northeastern TP, play a crucial role in decadal warming over the TP. And the Rossby wave trains are mainly modulated by interdecadal increases in Labrador Sea surface temperature.